Televisão e saúde: os temas ligados à qualidade de vida no telejornal Jornal Anhanguera primeira edição da TV Anhanguera - Santana, Bernadete Coelho de Sousa (2013)
This work presents a contribution will survey the airing of issues related to health and quality of life within the framework More Health appears on the newscast J. A. first edition of the TV Anhanguera affiliate of Rede Globo in Goiás This work brings some concepts of Communication, Journalism and Citizenship and presents reflections on the phenomenon of serving the health issues related quality of life while on TV and the possibility of promoting citizenship. The research is intended to show how the behavior of the professionals involved in the production process, reporting and display of the frame can influence and promote citizenship of viewers, even in a commercial enterprise where the focus is the audience.